KARAKTERISASI ISOLAT JAMUR AKAR ANGGREK SEBAGAI BAHAN AJAR LEAFLET UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMK PADA SUBTEMATIK KINGDOM FUNGI - Fitriya Ayu Wulandari; Dwi Sucianingtyas Sukamto; Hanif Rafika Putri (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to identify mycorrhizal fungi, primarily from the genera Rhizoctonia and Tulasnella, on orchid roots and develop leaflet-based teaching materials using the Research and Development (R&D) model with the 4D approach (Define, Design, Develop, Disseminate). Fungal identification was conducted through microscopic examination and molecular techniques (ITS rDNA sequencing) to ensure accurate classification. The 4D model involved defining student needs, designing leaflet content focused on fungal symbiosis, developing draft materials, and disseminating the final leaflet for classroom use. The effectiveness of the leaflet was evaluated with 40 students through pre- and post-tests measuring knowledge of fungal roles in orchid growth. Results showed the average pre-test score increased from 48.5 to 85.2 in the post-test, with an N-Gain score of 0.722 (72.29%), indicating moderate effectiveness. Improvements were most notable in students’ understanding of fungal identification and symbiotic functions. These findings demonstrate that leaflet-based teaching materials developed from precise fungal identification can significantly enhance student comprehension of Kingdom Fungi concepts.